Different Influence Analysis of Sunset Policy and Tax Amnesty to the Retailer/ Small and Medium Sized Enterprise Individual Taxpayer Compliance (in the Region of Majalaya Tax Office, Bandung City) - Yuliana Gunawan; Lidya Agustina; Enrico Goiyardi (EAJ (Economic and Accounting Journal), 2019)
As we all know, tax is one of the most essential source of a state income which reaches up to 70% of the total. The target of tax payment has always increased every year, together with the increasing need of state expenses. Many breakthrough has been made since the onset of tax reformation in 2002 in order to facilitate the tax payers in fulfilling their duty as well as to reach the target of tax proceeds.One of those breakthrough is Sunset Policy, and the other is Tax Amnesty. The Population used in this research is non -employee individual taxpayer enlisted in the Tax Office of Majalaya, Bandung City, using qualitative data (the primary data obtained from questionnaire result). Sampling data drawn from simple random sampling method. Data analysis method used is the Simple Regression analysis which has passed the validity, reliability and classical assumption tests combined t-test.The result of this research shows that there is a significant influence of both Sunset Policy and Tax Amnesty variable to the tax compliance of the individual tax payer, with the Sunset Policy conveys greater impact than the latter.Key words: tax amnesty, sunset policy, tax compliance of the individual tax payer